Application-Assisted PBL-STEM Model Hinbiodiv to Improve Students' Science Literacy in Biodiversity Material - Purwaningsih, Indri; Isnaeni , Wiwi; Marianti, Aditya; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2024)
The low level of students' scientific literacy is one of the problems that needs to be solved. This study aims to analyze the application of the Hinbiodiv-assisted PBL-STEM model in improving students' scientific literacy in biodiversity material in high school. The research method used is a quasi-experimental design with a nonequivalent control group design. The research sample included class X MIPA 4 as a control class totaling 37 students and class X MIPA 1 as an experimental group totaling 34 students. The data collected were in the form of increasing students' scientific literacy by distributing questionnaires to students. The data analysis of this study used the normality test, Walcaxon test, Man Whitney test, and N-Gain test. The results showed that the Implementation of the Hinbiodiv-Assisted PBL-STEM Model could improve students' scientific literacy in the experimental class with an N-Gain value of 0.79 in the high category, while in the control class with the conventional method the N-Gain value was 0.46 in the moderate category. So it can be concluded that the application of the Hinbiodiv-Assisted PBL-STEM Model is recommended for use in biology learning in high school to improve scientific literacy.